The Influence Of Product Quality, Price, And Brand Image On Fore Coffee Consumer Loyalty In The City Of Surabaya - Rizqia Khairunnisa Wibowo; Siti Ning Farida (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The competition for the modern coffee industry in Indonesia is getting tighter, so companies need to increase consumer loyalty. Fore Coffee is one of the fastest-growing local coffee brands, but based on the Top Brand Index 2023-2025, its position is still below several main competitors. This condition shows that Fore Coffee's consumer loyalty still needs to be improved and is allegedly influenced by product quality, price, and brand image. This study aims to analyze the influence of product quality, price, and brand image on Fore Coffee consumer loyalty in the city of Surabaya. The research uses a quantitative approach with a type of causal associative research. The research sample amounted to 150 respondents who were selected using accidental sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results showed that product quality, price, and brand image simultaneously had a positive and significant effect on consumer loyalty (F = 253,941; sig. = 0.000). Partially, product quality (t = 15,307), price (t = 12,449), and brand image (t = 10,813) also had a positive and significant effect with a significance value of 0.000. The value of the determination coefficient (R²) of 0.839 indicates that the three variables are able to explain 83.9% of the variation in consumer loyalty. The results of the study confirm that improving product quality, setting appropriate prices, and strengthening brand image play an important role in increasing Fore Coffee consumer loyalty in the city of Surabaya.